The Implementation of the Student Teams Achievement Division (STAD) Cooperative Learning Model Assisted by the Wayground Application to Improve Grade X Students’ Mathematics Learning Outcomes - Rosmita Sari; Yuliani Fitri; Refnywidialistuti Refnywidialistuti (The Future of Education Journal, 2026)
This study was motivated by the low mathematics learning outcomes of Phase E students in Office Management and Business Services (MPLB) at SMK Negeri 2 Padang, which were caused by conventional learning practices and the lack of technology use in learning evaluation. This study aims to determine whether the mathematics learning outcomes of students taught using the Student Teams Achievement Division (STAD) cooperative learning model assisted by the Wayground application are better than those of students taught using conventional learning. This research is a quasi-experimental study using the Randomized Control Group Only Posttest Design. The population of this study consisted of all Phase E MPLB students at SMK Negeri 2 Padang in the 2025/2026 academic year. The research sample consisted of an experimental class taught using the STAD cooperative learning model assisted by the Wayground application and a control class taught using conventional learning. The research instrument used was an essay-type mathematics learning outcome test. The learning outcome data were analyzed using the Mann-Whitney U test because both sample classes were not normally distributed. Based on the analysis results, the value of of  was 2.25, while the  value at the significance level of α = 0.05 was 1.65. Since ,  was rejected and  was accepted. Therefore, it can be concluded that the mathematics learning outcomes of students taught using the STAD cooperative learning model assisted by the Wayground application are better than those of students taught using conventional learning.